The costs of treatment resistant depression: evidence from a survey among Italian patients. (3rd April 2022) - Ruggeri, Matteo; Drago, Carlo; Mandolini, Donatella; Francesa Morel, Pier; Mencacci, Claudio; Starace, Fabrizio
ABSTRACT: Introduction: Treatment resistant depression (TRD) is a severe form of major depressive disorder associated with high symptoms severity, disability, and health resource utilization. Aim: The purpose of this study is to estimate the coss of TRD in Italy Methods: The study was carried on a sample of Italian patients diagnosed with TRD in 2019. In total, 306 observations were collected. The first step was to estimate the health and social costs of TRD resulting from the survey applying the Italian tariffs, daily wages, and prices. Secondly, we focused on the determinants of out of pocket expenditure (OOPE). A parametric analysis was performed to explore the association between the costs of TRD and a set of co-variates. Results: In total, the average healthcare costs were €2, 653. A national average of 42 lost working days was estimated resulting in a total cost of €7, 140 per patient. Regarding OOPE an average of € 615 per patient was found. Regression results showed how relevant regional gradients are likely to affect the amount of OOPE for TRD. Conclusions: the study confirms the important burden of TRD in Italy with specific focus on out of pocket expenditure. High heterogeneity is shown concerning regional settings.